TRAFFIC FLOW MODEL AND SHOCKWAVE ANALYSIS - Rompis, Semuel Y. R. (JURNAL SIPIL STATIK, 2018)
The flow, density and speed relationship is one among other most important element in traffic flow theory. There are many models that express the relationship between these three traffic stream primary elements. The first three models which have been used most commonly in traffic engineering practice are Greenshields, Greenberg and Underwood models. This study has built traffic flow model base on those models and decided the best model to represent the field data. The characteristic of the traffic flow will be obtained based on the chosen model, then using this information and an incident scenario a macroscopic shockwave analysis was conducted. The result of analysis, particularly the queue length, was compared to one obtained from simulation built in VISSIM.Â Key words: traffic flow, density, speed, macroscopic shockwave analysis, VISSIM